PERAN PROGRAM KIP DALAM SKEMA PENANGGULANGAN KEMISKINAN DI BIDANG PENDIDIKAN - Annisa, Wahid; Badrudin, Badrudin; Ulfiah, Ulfiah (ILJ: Islamic Learning Journal, 2024)
Education is the primary key to harnessing the potential of communities and alleviating poverty in Indonesia. The Kartu Indonesia Pintar (KIP) program has proven to be an effective solution in this endeavor. This research aims to analyze the impact of the KIP Program on education and poverty alleviation. A literature review method was employed to gather and analyze data from various sources, including academic studies, government reports, and scholarly articles. The research findings reveal that the KIP Program has provided improved access to education for impoverished communities, increasing school participation rates and reducing dropout rates. This has positively influenced the enhancement of the quality of life and a decrease in poverty rates in Indonesia. The KIP Program emerges as a potential solution capable of reshaping the future of education and poverty in the country. In addition, the research results also demonstrate that the KIP Program has a positive impact in raising the educational standards of the population, with increased high school graduation rates and higher rates of college enrollment. Furthermore, the program has contributed to enhancing awareness of the importance of education among disadvantaged communities. Therefore, the KIP Program has successfully integrated sustainable educational solutions and plays a pivotal role in poverty alleviation efforts in Indonesia.